A load-bearing wave-transparent ablative heat-protection anti-reconnaissance integrated composite radome structure and a preparation method thereof

CN122889995APending Publication Date: 2026-10-09CHENGDU TIANQIN ZHIHE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611141973.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0007]综上所述,现有天线罩技术在承载与透波的协同优化、高温环境下的粘接可靠性、耐烧蚀性能、涂层的高温稳定性及反侦察能力等方面仍存在不足,亟需一种兼具承载、透波、耐高温、抗烧蚀及反侦察功能的综合性能优异的天线罩结构方案

Benefits of technology

[0028](1)本发明通过结构创新、材料改性与工艺集成,在极端环境适配性、多功能协同性及实用经济性上实现多重突破。通过聚硅氮烷-丙烯酸树脂复合涂层与纳米ZrO2的协同作用,在1500℃、0.5s瞬时尾焰冲击下无导电碳层生成,介电常数稳定在2.6~3.2,介电损耗低于0.008,透波损耗率小于5%,彻底解决了传统陶瓷基、酚醛基及树脂基天线罩高温碳化导致透波失效的痛点,保障了极端高温下透波性能的稳定可靠。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889995A_ABST
    Figure CN122889995A_ABST
Patent Text Reader

Abstract

The application discloses a kind of bearing wave-transparent ablative heat-protection anti-reconnaissance integrated composite radome structure and preparation method, comprising: inner skin, the outer wall of inner skin is coated with first adhesive layer, and the outer wall of first adhesive layer is bonded with interlayer material, the outer wall of interlayer material is coated with second adhesive layer, the outer wall of second adhesive layer is bonded with outer skin, and the outer wall of outer skin is sprayed with anti-reconnaissance carbon-free coating. Through the structure of inner skin and wave-transparent integrated design, the coordination of mechanical and electrical properties is realized, the adhesive layer uses composite film system, maintains adhesive integrity and resists thermal shock at high temperature, the interlayer material has light weight, heat insulation and support function, effectively reduces weight and buffers thermal stress, the outer skin forms a protective layer by modifying filler, significantly improves ablative resistance and interfacial adhesion, the surface coating utilizes ceramic conversion and thermal reflection mechanism, realizes high-temperature carbon-free, non-conductive phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of antenna technology, specifically a composite material radome structure and preparation method that integrates wave transmission, ablation protection, heat protection, and counter-reconnaissance. Background Technology

[0002] Radomes are crucial electromagnetic wave-transmitting windows for aircraft, missiles, and other equipment to perform tasks such as communication, detection, fire control, and IFF (Identification Friend or Foe). They protect radar antennas or the entire microwave system to ensure normal operation in harsh environments and allow electromagnetic waves to pass through normally. With the rapid development of modern avionics technology and the continuous increase in missile flight speed, radomes not only need to have excellent wave transmission performance but must also possess multiple functions such as load-bearing, heat protection, heat insulation, and resistance to airflow erosion. High-performance radar radomes have become an integral and important component of aircraft, missiles, and other weapon systems.

[0003] Currently, resin-based structural / wave-transparent composite materials have become the main materials for manufacturing various radar radomes due to their excellent dielectric, mechanical, temperature resistance, and processability properties. Among them, quartz fiber, with its outstanding dielectric, mechanical, and heat resistance properties, has been widely used in various high-performance radar radomes. Regarding resin matrices, cyanate ester resins and their modified systems have attracted attention due to their combination of good dielectric and mechanical properties.

[0004] In terms of structural design, to achieve broadband wave transmission, radomes often employ sandwich structures such as A-layer and B-layer, consisting of a low-dielectric-constant intermediate core layer (foam or honeycomb) and inner and outer skin layers. Commonly used core layer materials include PMI foam and aramid paper honeycomb. However, the bonding reliability of existing sandwich structure radomes in high-temperature environments remains insufficient, and the interface between the skin and the core layer is prone to debonding under repeated thermal shock conditions.

[0005] Regarding high-temperature resistance, with increasing flight speeds, the intense aerodynamic heat presents radomes with extremely high temperature challenges. Currently, high-temperature transparent radome materials mainly employ quartz fiber reinforced composite materials or ceramic matrix composite materials. However, due to limitations in processing technology, most high-temperature transparent radomes adopt a homogeneous structure (half-wavewall design), exhibiting narrow-band transmission characteristics, which is insufficient to meet broadband transmission requirements. Furthermore, the ablation resistance of existing outer skin materials still needs further improvement.

[0006] In terms of coating protection, the surface coating of the radome needs to simultaneously meet multiple requirements such as wave transmission, high temperature resistance, and ablation resistance. Existing coating systems are prone to carbonization or the formation of conductive phases at high temperatures, affecting wave transmission performance, and the adhesion between the coating and the substrate is insufficient, making it prone to cracking and peeling under thermal shock conditions. In addition, with the increasing urgency of stealth requirements, the radome also faces the requirement of reducing the radar cross section (RCS) for counter-surveillance.

[0007] In summary, existing radome technologies still have shortcomings in terms of synergistic optimization of load-bearing and wave transmission, bonding reliability under high-temperature environments, ablation resistance, high-temperature stability of coatings, and anti-reconnaissance capabilities. There is an urgent need for a comprehensive radome structure solution with excellent integrated performance that combines load-bearing, wave transmission, high-temperature resistance, ablation resistance, and anti-reconnaissance capabilities. Summary of the Invention

[0008] The technical solution adopted in this invention is as follows: A composite material radome structure that integrates wave-transmitting ablation protection, heat protection, and counter-reconnaissance capabilities, comprising:

[0009] Inner skin;

[0010] The outer wall of the inner skin is coated with a first adhesive layer, and an interlayer material is bonded to the outer wall of the first adhesive layer. The outer wall of the interlayer material is coated with a second adhesive layer, and the outer skin is bonded to the outer wall of the second adhesive layer. The outer wall of the outer skin is sprayed with a non-carbonized anti-reconnaissance coating.

[0011] Furthermore, the inner skin is a low-dielectric high-temperature epoxy / modified cyanate quartz prepreg with a thickness of 0.2–2.0 mm.

[0012] Furthermore, both the first adhesive layer and the second adhesive layer are composite systems of cyanate ester film and epoxy modified film, with an interlayer shear strength ≥22MPa and a thickness of 0.05~0.35mm.

[0013] Furthermore, the interlayer material is aramid paper honeycomb or PMI foam, with a density of 48–110 kg / m³ and a thickness of 0.5–50 mm.

[0014] Furthermore, the outer skin is a nano-WO3 modified phenolic quartz composite material, containing 10wt% nano-WO3 and SiC composite filler, with a linear ablation rate of 0.08mm / s and a thickness of 0.2-2.0mm.

[0015] Furthermore, the anti-reconnaissance non-carbonized coating is composed of the following components by mass percentage: 40% polysilazane, 30% acrylic resin, 3% nano-ZrO2 modified with a polymeric dispersant, 5% hollow glass microspheres with a particle size of 5-10 μm, 2% nano-WO3 with a particle size of 50-100 nm, 3% glass flakes, 2% coupling agent KH-560, and 15% composite solvent, wherein the composite solvent is a 1:1 mass ratio mixture of xylene and cyclohexanone; the thickness of the anti-reconnaissance non-carbonized coating is 0.1-5 mm, and it does not carbonize or generate a conductive phase at a transient high temperature of 1500℃ for 0.5 s.

[0016] Furthermore, the radome structure maintains a dielectric constant of 2.6~3.2, dielectric loss <0.008, and transmission loss rate <5% under the impact of a 1500℃, 0.5s instantaneous exhaust flame, and exhibits an attenuation of ≥15dB in the X-band radar cross-section.

[0017] Furthermore, the fiber layup angle of the inner skin is selected from one or more combinations of 0°, ±15°, ±30°, ±45°, and ±90°.

[0018] A method for fabricating a composite material radome structure that supports wave transmission, ablation, heat protection, and counter-reconnaissance, applicable to any one of the above-mentioned composite material radome structures, includes the following steps:

[0019] S1: Provide molding molds, clean the mold surfaces and apply release agent;

[0020] S2: Lay out the prepreg fabric of the inner skin, the first adhesive layer, the interlayer material, the second adhesive layer, and the prepreg fabric of the outer skin according to the designed lay-up sequence and fiber angle, compact the layers, and use a vacuum bag film to vacuum and compact every 1 to 2 layers.

[0021] S3: After the layup is completed, the entire structure is vacuumed and co-cured in an autoclave in one step.

[0022] S4: After curing, the surface of the outer skin is polished and then sprayed with a non-carbonized anti-reconnaissance coating to obtain the radome.

[0023] Furthermore, in step S1, the release agent is applied 3 to 5 times, with an interval of 10 to 15 minutes between each application;

[0024] In step S2, the operating ambient temperature is 30±5℃, and the vacuum degree of the vacuum pump is <-0.085MPa.

[0025] During co-curing in step S3, the gelation time of different resin systems is similar under isothermal conditions;

[0026] In step S4, the thickness of the anti-reconnaissance non-carbonized coating is 0.1–5 mm.

[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] (1) This invention achieves multiple breakthroughs in extreme environment adaptability, multifunctional synergy, and practical economy through structural innovation, material modification, and process integration. Through the synergistic effect of polysilazane-acrylic resin composite coating and nano ZrO2, no conductive carbon layer is generated under the impact of a 0.5s instantaneous tail flame at 1500℃, the dielectric constant is stable at 2.6~3.2, the dielectric loss is less than 0.008, and the wave transmission loss rate is less than 5%. This completely solves the problem of wave transmission failure caused by high-temperature carbonization of traditional ceramic-based, phenolic-based, and resin-based radomes, and ensures the stable and reliable wave transmission performance under extreme high temperatures.

[0029] (2) The present invention uses nano WO3 to carry out a two-stage modification design in the outer skin and surface coating, achieving a radar cross section attenuation of ≥15dB in the commonly used X-band of UAVs, without sacrificing the wave transmission performance, breaking through the technical bottleneck of "wave transmission and stealth cannot be achieved at the same time". Traditional ceramic-based radomes require additional spray coating and have poor bonding force, while traditional resin-based radomes have no anti-reconnaissance function. The present invention significantly improves the concealment and security of the launch process.

[0030] (3) The sandwich structure of the present invention, combined with aramid paper honeycomb or PMI foam core and cyanate ester-epoxy composite adhesive layer, effectively buffers the severe temperature difference stress between 1500℃ high temperature and room temperature, avoiding the brittle cracking of ceramic-based radomes and the delamination problem of phenolic and resin-based radomes. It can withstand ≥12 repeated thermal shocks, and maintenance only requires high-pressure air blowing cleaning. Compared with single-use resin-based radomes and easily damaged ceramic-based radomes, the operation and maintenance cost is reduced by more than 60%, which greatly improves the reliability and economy of repeated use.

[0031] (4) The density of the sandwich material of the present invention is only 48-110 kg / m³, making the overall density of the radome ≤1.2 g / cm³, which is much lower than the ≥2.5 g / cm³ of the ceramic-based radome. While ensuring the load-bearing strength (tensile strength ≥65 MPa), it significantly reduces the load burden on the launch vehicle, solves the problem of the traditional heavy radome affecting the mobility of the launch vehicle, and is highly adaptable to the flexible deployment requirements.

[0032] (5) The present invention adopts the preparation method of integral curing molding of positive mold in autoclave, combined with precise spraying of anti-reconnaissance non-carbonized coating. The overall process is mature and can effectively adapt to complex curved surface molding. Compared with the high cost and complex molding of ceramic-based antenna radome, it has more advantages in large-scale production, high cost performance, and meets the requirements of rapid response and batch matching of launch vehicle. Attached Figure Description

[0033] Figure 1 This is a schematic diagram of the antenna radome structure of the present invention;

[0034] Figure 2 This is an enlarged cross-sectional view of invention A;

[0035] Figure 3 This is a top view of the molding die of the present invention;

[0036] Figure 4 This is a cross-sectional view of the antenna radome mold of the present invention;

[0037] Figure 5 This is a cross-sectional view of the molding die of the present invention.

[0038] The markings in the diagram are: 1. Inner skin; 2. Outer skin; 3. Second adhesive layer; 4. Interlayer material; 5. Anti-reconnaissance non-carbonized coating; 101. First adhesive layer. Detailed Implementation

[0039] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0040] Example 1

[0041] Reference Figure 1 - Figure 5 A composite material radome structure integrating wave transmission, ablation protection, heat protection, and counter-reconnaissance capabilities includes: an inner skin 1, the outer wall of which is coated with a first adhesive layer 101, and an interlayer material 4 is bonded to the outer wall of the first adhesive layer 101; the outer wall of the interlayer material 4 is coated with a second adhesive layer 3; the outer skin 2 is bonded to the outer wall of the second adhesive layer 3, and a non-carbonized counter-reconnaissance coating 5 is sprayed onto the outer wall of the outer skin 2. Through the integrated layered layout of the inner skin, adhesive layer, interlayer material, outer skin, and non-carbonized counter-reconnaissance coating, the load-bearing, heat insulation, heat protection, and counter-reconnaissance functions are distributed to different layers. Each layer works synergistically and complementarily. While ensuring the overall rigidity and load-bearing capacity of the structure, the interlayer structure achieves lightweighting, and the multi-layer interface effectively blocks thermal shock and buffers stress, avoiding cracking and delamination. It has the advantages of both functional integration and structural integrity.

[0042] Reference Figure 1 - Figure 5The inner skin 1 is made of low-dielectric, high-temperature epoxy / modified cyanate quartz prepreg fabric, which has both primary load-bearing and high wave transmission functions. The thickness is designed to be 0.2-2.0mm, and the fiber angle can be flexibly selected according to the stress and wave transmission requirements, such as 0°, ±15°, ±30°, ±45°, ±90°, etc., to ensure a balance between mechanical strength and transmission efficiency. The first adhesive layer 101 and the second adhesive layer 3 are both adhesive layers. Both the first adhesive layer 101 and the first adhesive layer 3 adopt a "cyanate ester film + epoxy modified film" composite system. The cyanate ester film ensures low dielectric properties, while the epoxy modified film improves high-temperature bonding toughness. After lamination, the material exhibits no softening or debonding under instantaneous high temperature of 1500℃, with an interlaminar shear strength ≥22MPa and a thickness controlled between 0.05 and 0.35mm. This meets the structural integrity requirements under repeated thermal shock. The sandwich material 4 is made of aramid paper honeycomb or PMI foam, with a density of approximately 48–110 kg / m³. It plays a crucial role in "lightweighting, thermal insulation, and structural support," significantly reducing the overall weight of the radome to meet the mobility requirements of the launch vehicle. It also effectively blocks high-temperature conduction, buffers thermal shock stress, and enhances overall rigidity. The thickness ranges from 0.5 to 50mm and can be flexibly adjusted according to design requirements. Skin 2 uses nano-WO3 modified phenolic quartz composite material, with 10wt% nano-WO3 and SiC composite filler added. At high temperature, a dense SiO2-WO3-SiC composite protective layer is formed, reducing the linear ablation rate to 0.08mm / s, improving ablation resistance by 30% compared to traditional materials. It also strengthens the adhesion to the surface coating. The thickness is designed to be 0.2–2.0mm. The anti-reconnaissance non-carbonized coating 5 has the following formulation: the matrix resin is 40% polysilazane + 30% acrylic resin; the non-carbonized filler contains 3% nano-ZrO2 modified with a polymer dispersant and 5% particles with a particle size of 5–10μm. The coating consists of hollow glass microspheres with a particle size of m; the anti-reconnaissance filler is 2% nano-WO3 with a particle size of 50-100nm (to achieve low RCS) and 3% glass flakes to enhance density; the additives are 2% coupling agent (KH-560) and 15% composite solvent (xylene:cyclohexanone = 1:1). Its carbonization-free mechanism is as follows: at high temperature, polysilazane is converted into SiCN ceramic phase, and nano-ZrO2 forms a heat reflection barrier, which synergistically prevents resin carbonization; acrylic resin improves the toughness of the coating and avoids cracking, ultimately achieving no carbonization and no conductive phase generation at an instantaneous high temperature of 1500℃ / 0.5s, with a coating thickness of 0.1-5mm.

[0043] Reference Figure 1 - Figure 5A method for preparing a composite material radome structure that supports wave transmission, ablation, heat protection, and counter-reconnaissance, applicable to any one of the above-mentioned composite material radome structures, includes the following steps: the inner skin 1, first adhesive layer 101, interlayer material 4, second adhesive layer 3, and outer skin 2 of the radome are integrally cured in an autoclave to ensure structural integration and dimensional accuracy; the molding mold consists of an radome profile mold, a demolding bolt, a demolding plate, a molding mold base plate, and a lifting ring; the radome profile mold and the molding mold base plate are welded together; before laying, the radome is cleaned with acetone and dried, then 3-5 coats of high-efficiency release agent are applied (each 10-15 minutes apart), and the demolding plate is then attached to the molding mold. After assembly on the base plate, the prepreg, adhesive layer, and sandwich layer, cut by an automatic fabric cutting machine, are laid out according to the designed fiber angle and thickness. The operating environment is controlled at a temperature of 30±5℃. Layers are laid one by one, and the layers are compacted with rollers. Every 1-2 layers, vacuum bags are laid out and vacuumed to compact the layers. The entire system is vacuumed to a vacuum degree of <-0.085MPa. The system is formed in one step using an autoclave. The curing process varies depending on the resin system. For two or more resin systems, the gel time under isothermal conditions must be similar for one-time co-curing. After curing, the surface is polished and then a non-carbonized anti-reconnaissance coating is precisely sprayed on. Finally, a functionally synergistic and high-performance extreme environment-adaptable radome is formed, which fully meets the multiple usage requirements of the launch vehicle under close-range exhaust plume impact.

[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A composite material radome structure that integrates wave-transmitting, ablation-resistant, heat-resistant, and counter-reconnaissance capabilities, characterized in that: include: Inner skin (1); The outer wall of the inner skin (1) is coated with a first adhesive layer (101), and an interlayer material (4) is bonded to the outer wall of the first adhesive layer (101). The outer wall of the interlayer material (4) is coated with a second adhesive layer (3), and an outer skin (2) is bonded to the outer wall of the second adhesive layer (3). The outer wall of the outer skin (2) is sprayed with an anti-reconnaissance non-carbonized coating (5).

2. The integrated composite material radome structure for wave transmission, ablation protection, heat protection, and counter-reconnaissance as described in claim 1, characterized in that, The inner skin (1) is a low dielectric high temperature epoxy / modified cyanate quartz prepreg with a thickness of 0.2 to 2.0 mm.

3. The integrated composite material radome structure for wave transmission, ablation protection, heat protection, and counter-reconnaissance as described in claim 1, characterized in that, Both the first adhesive layer (101) and the second adhesive layer (3) are composite systems of cyanate ester film and epoxy modified film, with an interlayer shear strength ≥22MPa and a thickness of 0.05~0.35mm.

4. The integrated composite material radome structure for wave transmission, ablation protection, heat protection, and counter-reconnaissance as described in claim 1, characterized in that, The interlayer material (4) is aramid paper honeycomb or PMI foam with a density of 48-110 kg / m³ and a thickness of 0.5-50 mm.

5. The integrated composite material radome structure for wave transmission, ablation protection, heat protection, and counter-reconnaissance as described in claim 1, characterized in that, The outer skin (2) is a nano-WO3 modified phenolic quartz composite material containing 10wt% nano-WO3 and SiC composite filler, with a linear ablation rate of 0.08mm / s and a thickness of 0.2~2.0mm.

6. The integrated composite material radome structure for wave transmission, ablation protection, heat protection, and counter-reconnaissance as described in claim 1, characterized in that, The anti-reconnaissance non-carbonized coating (5) is composed of the following components by mass percentage: 40% polysilazane, 30% acrylic resin, 3% nano ZrO2 modified by polymer dispersant, 5% hollow glass microspheres with a particle size of 5~10μm, 2% nano WO3 with a particle size of 50~100nm, 3% glass flakes, 2% coupling agent KH-560, and 15% composite solvent, wherein the composite solvent is a mixture of xylene and cyclohexanone in a 1:1 mass ratio; the thickness of the anti-reconnaissance non-carbonized coating (5) is 0.1~5mm, and it does not carbonize or generate a conductive phase at a high temperature of 1500℃ for 0.5s.

7. The integrated composite material radome structure for wave transmission, ablation protection, heat protection, and counter-reconnaissance as described in claim 1, characterized in that, The radome structure maintains a dielectric constant of 2.6~3.2, dielectric loss <0.008, and transmission loss rate <5% under the impact of a 1500℃, 0.5s instantaneous exhaust flame. Furthermore, it exhibits an attenuation of ≥15dB in the X-band radar cross-section.

8. The integrated composite material radome structure for wave transmission, ablation protection, heat protection, and counter-reconnaissance as described in claim 2, characterized in that, The fiber layup angle of the inner skin (1) is selected from one or more combinations of 0°, ±15°, ±30°, ±45°, and ±90°.

9. A method for fabricating an integrated composite material radome structure that supports wave transmission, ablation, heat protection, and counter-reconnaissance, characterized in that, The method applied to the integrated composite material radome structure for wave transmission, ablation protection, heat protection, and counter-reconnaissance as described in any one of claims 1-8 includes the following steps: S1: Provide the molding die, clean the mold surface and apply release agent; S2: Lay out the prepreg of the inner skin (1), the first adhesive layer (101), the interlayer material (4), the second adhesive layer (3), and the prepreg of the outer skin (2) according to the designed lay-up sequence and fiber angle, compact the layers, and use vacuum bags to vacuum and compact every 1 to 2 layers. S3: After the layup is completed, the entire structure is vacuumed and co-cured in an autoclave in one step. S4: After curing, the surface of the outer skin (2) is polished and then sprayed with a non-carbonized anti-reconnaissance coating (5) to obtain the antenna radome.

10. The method for preparing a composite material radome structure with wave-transmitting, ablation-resistant, heat-resistant, and counter-reconnaissance capabilities according to claim 9, characterized in that, In step S1, the release agent is applied 3 to 5 times, with an interval of 10 to 15 minutes between each application. In step S2, the operating ambient temperature is 30±5℃, and the vacuum degree of the vacuum pump is <-0.085MPa. During co-curing in step S3, the gelation time of different resin systems is similar under isothermal conditions; The thickness of the anti-reconnaissance non-carbonized coating (5) in step S4 is 0.1-5 mm.